Deportation Deadline - Andrew Tae-Hyun Kim (Washington University Law Review, 2017)
Deadlines regulate nearly all facets of life. In U.S. law, deadlines control the timeliness of a claim in the forms of statutes of limitations and common law doctrines such as laches. In nearly all areas of the law, whether involving claims brought by private actors or the government, and in both criminal and civil contexts, an expiration date cuts off a plaintiff’s right to assert a claim. No such deadline exists, however, for immigration enforcement actions. The U.S. government can deport immigrants for offenses after decades have passed. As a result, millions of long-term, otherwise law-abiding and productive individuals participating and residing in communities across this nation live under an indefinite threat of deportation for conduct that may have happened decades ago. This Article exposes and examines this procedural anomaly between immigration and non-immigration law, which is yet another aspect of U.S. immigration law that makes it exceptional precisely because of the subject it regulates— noncitizens. In this Article, I frame the argument for nuanced deportation deadlines by drawing on comparative insights from other areas of the law, where statutes of limitations represent the legal norm, and import these insights into the immigration enforcement context. I locate the precedent for a deportation deadline in the early immigration statutes enacted at the turn of the century and in the historical remnants of that approach in the traces of mercy that animate the current immigration statute. Finally, I outline how a statute of limitations could be realized in the deportation context, and, in the process, propose time limitations on deportations as an important strategy for integrating long-term undocumented immigrants into U.S. society.
Keywords: statute of limitations; deport; deportation; immigration; accrual rule; discovery rule; liminal status